DINAMICA DEZVOLTĂRII ALGELOR CHLORELLA VULGARIS ŞI SYNECHOCYSTIS SALINA PE MEDII CU ADAOS DE APE REZIDUALE DE CANALIZARE DE LA STAŢIA DE EPURARE DIN mun. CHIŞINĂU - USM ADMIN (Studia Universitatis Moldaviae: Stiinte reale si ale naturii, 2007)
This article includes the research results about the dinamic development of algaes Chlorella vulgaris and Synechocystis salina of medium with addition residue water of the cleaning station of Chisinau municipality.